Etymological Aspects of Idiomatic and Proverbial Expressions in the Lexicographic Development of Sesotho sa Leboa ? A Semantic Analysis* - V.M. Mojela (Lexikos, 2011)
Abstract: Idiomatic and proverbial expressions are important components of the oral traditionof Sesotho sa Leboa, and therefore a knowledge of the literal meaning of words as they appear indictionaries without inclusion of their figurative meaning seems to be a shortcoming. An idiom or aproverb possesses one basic meaning, i.e. the meaning to which the idiom or proverb is basicallymeant to refer, but each idiom or proverb is made up of several lexical items. Each of these lexicalitems has its own meaning, which usually differs from the figurative sense of the idiom or proverb.Even though the meaning of the words in an idiomatic or proverbial expression seems to differfrom the sense of the idiom or proverb, there is to a certain extent a relationship. It is this relationshipwhich lexicographers can assist to explain in their definitions in order to clarify both the literaland the figurative meanings of words in Sesotho sa Leboa.This article aims to stress the importance of having specialized dictionaries which will giveusers detailed etymological explanations of the meaning of idiomatic and proverbial expressions asused in Sesotho sa Leboa. The etymological analysis of the meaning of these lexical items (idiomsand proverbs) will provide a better understanding of these expressions and enrich dictionarieswith detailed definitions. This will create a better understanding of the relationship between theliteral meanings of the expressions and their real (i.e. figurative) meanings. Keywords: DIACHRONIC ANALYSIS, ETYMOLOGY, FIGURATIVE EXPRESSION, IDIOM,LEMMATIZATION, LEXICOLOGY, METAPHOR, METAPHORIC EXPRESSION, PROVERB,SYNCHRONIC ANALYSIS, TERMINOGRAPHY. Opsomming: Etimologiese aspekte van idiomatiese en spreekwoordelikeuitdrukkings in die leksikografiese ontwikkeling van Sesotho sa Leboa — 'nsemantiese ontleding. Idiomatiese en spreekwoordelike uitdrukkings is belangrike komponentevan die mondelinge tradisie van Sesotho sa Leboa en gevolglik skyn die letterlike betekenisvan woorde soos hulle in woordeboeke voorkom sonder insluiting van hul figuurlike betekenis, 'ntekortkoming te wees. 'n Idioom of spreekwoord besit een basiese betekenis, d.i. die betekenis waarna die idoom of spreekwoord bedoel is om basies te verwys, maar elke idioom of spreekwoordbestaan uit verskeie leksikale items. Hierdie leksikale items het elk sy eie betekenis watgewoonlik verskil van die figuurlike betekenis van die idioom of spreekwoord. Selfs al skyn diebetekenis van die woorde in 'n idiomatiese of spreekwoordelike uitdrukking te verskil van dieidioom of spreekwoord, is daar in sekere mate 'n verwantskap. Dit is hierdie verwantskap watleksikograwe kan help om in hul definisies te verklaar ten einde sowel die letterlike as die figuurlikebetekenisse van woorde in Sesotho sa Leboa te belig.Die doel van hierdie artikel is om die belangrikheid te beklemtoon van die besit van gespesialiseerdewoordeboeke wat gebruikers uitvoerige etimologiese verklarings sal gee van idiomatieseen spreekwoordelike uitdrukkings soos in Sesotha sa Leboa gebruik. Die etimologiese ontledingvan hierdie leksikale items (idiome en spreekwoorde) sal 'n beter begrip van hierdie uitdrukkingsverskaf en woordeboeke met uitvoerige definisies verryk. Dit sal 'n beter begrip van die verhoudingtussen die letterlike betekenisse van die uitdrukkings en hul werklike (d.i. figuurlike) betekenissebewerkstellig. Sleutelwoorde: DIACHRONIESE ONTLEDING, ETIMOLOGIE, FIGUURLIKE UITDRUKKING,IDIOOM, LEKSIKOLOGIE, LEMMATISERING, METAFOOR, METAFORIESE UITDRUKKING,SINCHRONIESE ONTLEDING, SPREEKWOORD, TERMINOGRAFIE